DETRIMENTAL COMPLICATIONS OF MECONIUM ASPIRATION SYNDROME AND THEIR IMPACT ON OUTCOME - Shaikh, Mehmood; Waheed, Khwaja Ahmad Irfan; Javaid, Sulman; Gul, Rafia; Hashmi, Muhammad Almas; Fatima, Syeda Tanseen (Journal of Ayub Medical College Abbottabad, 2016)
Background: Meconium aspiration syndrome (MAS) is respiratory distress in an infant born through meconium stained amniotic fluid (MSAF) whose signs cannot be otherwise explained. MAS is associated with different complications. Many studies have been conducted in developed world to find the outcome associated with MAS but data from developing countries is lacking. Present study was conducted to determine the impact of chemical pneumonitis, pulmonary hypertension (PHN) and air leak on outcome of new-borns with MAS. Methods: This cross sectional descriptive study was conducted in a tertiary care Neonatology unit. The babies diagnosed with MAS were included in the study. All patients were monitored for development of complications. Outcome in terms of mortality was recorded. Outcome was compared by chi-square test and p-value <0.05 is considered significant. Results: Seventy two babies were included in the study. Mean gestation was 37±0.56 weeks and birth weight was 2.87±0.49 kg. Male to female ratio was 1.57:1 and mean age of admission was 9.59±5.27 hours. Chemical pneumonitis, PHN and chemical pneumonitis with PHN were observed in 23.6%, 20.8% and 26.4% neonates respectively. Mortality rate was 19.44%. The mortality was highest in babies having chemical pneumonitis with PHN (p-value=0.013) followed by chemical pneumonitis group (p-value=0.02) and PHN group (p-value=0.032). Conclusion: About three fourth babies with MAS developed one or more complications. Mortality is significantly increases with the development of complications so as more the complications more is the mortality. Keywords: Meconium Aspiration Syndrome; Chemical Pneumonitis; Persistent Pulmonary Hypertension.